Glycerol as a Substrate and Inactivator of Coenzyme B-12-Dependent Diol Dehydratase - Bilic, Luka; Baric, Danijela; Sandala, Gregory M.; Smith, David M.; Kovacevic, Borislav (Chemistry - A European Journal, 2021)
Diol dehydratase, dependent on coenzyme B-12 (B-12-dDDH), displays a peculiar feature of being inactivated by its native substrate glycerol (GOL). Surprisingly, the isofunctional enzyme, B-12-independent glycerol dehydratase (B-12-iGDH), does not undergo suicide inactivation by GOL. Herein we present a series of QM/MM and MD calculations aimed at understanding the mechanisms of substrate-induced suicide inactivation in B-12-dDDH and that of resistance of B-12-iGDH to inactivation. We show that the first step in the enzymatic transformation of GOL, hydrogen abstraction, can occur from both ends of the substrate (either C1 or C3 of GOL). Whereas C1 abstraction in both enzymes leads to product formation, C3 abstraction in B-12-dDDH results in the formation of a low energy radical intermediate, which is effectively trapped within a deep well on the potential energy surface. The long lifetime of this radical intermediate likely enables its side reactions, leading to inactivation. In B-12-iGDH, by comparison, C3 abstraction is an endothermic step; consequently, the resultant radical intermediate is not of low energy, and the reverse process of reforming the reactant is possible.
CRIS-Team WoS Importer:2021-05-14